PENGARUH PAD, DAU, SILPA DAN LUAS WILAYAH TERHADAP BELANJA MODAL - Afkarina, Zia; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of local own source revenue, general allocation fund, Surplusof Financing Budget and territory to the capital expenditure in the districts / citiesgovernment in EastJava province in 2012-2015 periods. The research method has been done by using purposive sampling with the numbersof samples are 148 financial statements from 38 districts / cities in all East Java provinces. The data is the secondary data has been obtained from the realization ofLocal Government Budget (APBD) of districts / cities in East Java Province with the observation period is 2012-2015 which has been obtained fromthe Audit Board of the Republic of Indonesia East Java Province. The result of this research which has been carried out by using multiple analysis shows that local own source revenue, general allocation fund and territorygive positive influence to the capital expenditure. Meanwhile, the remaining is Surplus of Financing Budget does not give any significant influence to the capital expenditure, with the R square 0.959 or 959%, shows that independent variablesgive influence to the dependent variable.Keywords: Local own sources, general allocation fund, Financing Budget Surplus area, capital expenditure.